2019
DOI: 10.3390/w11040633
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phosphates from Aqueous Solutions on Alginate/Goethite Hydrogel Composite

Abstract: The basic process to reduce the phosphate ions in aquatic environments is to move the phosphorus circulation processes on the water–sediment phase boundary towards depositing it in the solid phase through chemical precipitation or adsorption. Modern technologies for removal of phosphorus can be based on cheap and environmentally friendly natural polysaccharides modified with multivalent metals. In this study alginate/goethite hydrogel composite has been investigated for phosphate uptake from aqueous solutions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 53 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…A porous structure was previously reported for CMC-ALG beads (Kim et al, 2012). Fairly long equilibration times were reported for the sorption of phosphorus onto alginate/goethite composites (264 hr, (Siwek, Bartkowiak, & Włodarczyk, 2019)) and onto aluminum ALG-N-Isopropylacrylamide beads (14 hr, (Wan et al, 2016)). Despite the long equilibration times, even after 30 min, the mg PO 4 adsorbed/g sorbent were nearly doubled for ACMC beads (0.09 mg/g) than for POP powder (0.06 mg/g), as shown in Figure 6.…”
Section: Research Articlementioning
confidence: 61%
“…A porous structure was previously reported for CMC-ALG beads (Kim et al, 2012). Fairly long equilibration times were reported for the sorption of phosphorus onto alginate/goethite composites (264 hr, (Siwek, Bartkowiak, & Włodarczyk, 2019)) and onto aluminum ALG-N-Isopropylacrylamide beads (14 hr, (Wan et al, 2016)). Despite the long equilibration times, even after 30 min, the mg PO 4 adsorbed/g sorbent were nearly doubled for ACMC beads (0.09 mg/g) than for POP powder (0.06 mg/g), as shown in Figure 6.…”
Section: Research Articlementioning
confidence: 61%
“…According to their research, the peak at 170 • C presents the removal process of the lignite sulfonated humic acid functional group (hydroxyl, carboxyl, phenol hydroxyl group, etc.) [40,41]. In this study, peat sulfonated at a high temperature may trigger functional group desorption.…”
Section: The Selection Of the Sulfonated Peatmentioning
confidence: 80%
“…However, the modified peat exhibited a greater adsorption efficiency to Cr(VI) than the natural peat. Therefore, based on the above results, it is suggested that chemisorption dominated the adsorption process [1,40,42]. The FT-IR spectra of the natural, modified, and Cr-loaded modified peat are presented in Figure 3, wherein the band intensity of the modified peat was stronger than that of the natural one.…”
Section: Characterization Of Peat Samplesmentioning
confidence: 83%
See 2 more Smart Citations